Muslim women, domestic violence, and psychotherapy: theological and clinical issues - Isgandarova, Nazila (Routledge, 2019)
Introduction -- Defining Islamic psychotherapy in the context of the Islamic tradition -- Literature review: definitions/discussions of key concepts -- Divine testing and suffering -- Satanic interference and evil eye -- Spiritual diseases -- Honour and shame -- Future recommendations -- Conclusion